2006
DOI: 10.1007/s10979-006-9030-3
|View full text |Cite
|
Sign up to set email alerts
|

Appropriately Upset? Emotion Norms and Perceptions of Crime Victims.

Abstract: Victims who express less emotion in response to a crime are perceived as less deserving, less sympathetic, and they have less punishment assigned to the offender who committed the crime. This study considers the extent to which emotion norms underlie perceptions of victims who testify. Two studies investigate the circumstances in which emotional reactions to a crime are seen as "unusual" and whether a more general emotion norm underlies responses to victim testimony. We test a "victim-role" norm against a "pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 32 publications
(40 reference statements)
2
55
0
1
Order By: Relevance
“…Therefore, it appears likely that we have an inherent bias (consistent with expectations) that victims are to be emotional whereas the behaviour of perpetrators is less critical in case outcomes. Further, if these emotional responses are deemed "appropriate" in congruence with the level of severity of the crime, mock jurors are more likely to assign higher punitiveness ratings to alleged perpetrators (Rose, Nadler, & Clark, 2006). In our study, such polarized ratings may have been limited by the ambiguity of the sexual assault case presented, and the moderate level of severity of the crime (i.e., there was no extensive physical violence associated with the assault).…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, it appears likely that we have an inherent bias (consistent with expectations) that victims are to be emotional whereas the behaviour of perpetrators is less critical in case outcomes. Further, if these emotional responses are deemed "appropriate" in congruence with the level of severity of the crime, mock jurors are more likely to assign higher punitiveness ratings to alleged perpetrators (Rose, Nadler, & Clark, 2006). In our study, such polarized ratings may have been limited by the ambiguity of the sexual assault case presented, and the moderate level of severity of the crime (i.e., there was no extensive physical violence associated with the assault).…”
Section: Discussionmentioning
confidence: 73%
“…More specifically, when the victim impact statement was absent jurors were angrier with a male (versus female) defendant, but when the victim impact statement was present jurors were angrier with a female (versus) male defendant. Rose, Nadler, and Clark (2006), however, found that victim impact statements did not affect mock jurors' self-reported emotions. The discrepant findings might have to do with methodological differences between the types of case in the two studies: The latter study involved a victim's statement about a robbery, which might have elicited less emotion than the murder case used in the former study.…”
Section: Victim Impact Statementsmentioning
confidence: 83%
“…While a furrowed brow and downturned lip corners can corroborate the verbal exposition of remorse, guilt, and/or shame, the lack thereof may give the observer concern that the 1 Other evidence for emotion norms in apology contexts comes from the perspective of the victim. Rose, Nadler, and Clark (2006) find that victims are also expected to express appropriate levels of emotion, and that victims' emotional expressions impact observers' perceptions of them. apology is not driven by genuine emotion (Ekman, 1992;Porter & ten Brinke, 2008;Smith, 2008).…”
Section: The Role Of Perceived Sinceritymentioning
confidence: 87%